“Can Intelligence Make You Happy?” The Influence of Tourists’ Cultural Sustainability and Intelligence on Their Flow Experience - Boqian Wei (MDPI AG, 2021)
Chinese culture has been developed over five thousand years, and the ways in which to retain its sustainable development and maintain its rich spiritual treasures are critical issues. In order to address this critical issue, this study examines whether cultural intelligence can promote positive emotions and a flow experience. The results from 509 valid samples reveal that cultural intelligence contributes to a flow experience through a path of “perception–enjoyment–flow”. Cultural experience, perceived aesthetics, perceived authenticity and the awakening of enjoyment are effective conduction factors in the process. Furthermore, this study confirms that creative performance has a positive moderating effect on the relationship between cultural intelligence and cultural experience, perceived aesthetics, and perceived authenticity. The findings clarify the links of the influence of cultural intelligence on tourists’ flow experience, and expand the theoretical framework for research on flow experience and the scope of the application of flow theory.